Kartagener's Syndrome in Children - Sjawitri P. Siregar; I. Budiman; Nastiti Rahajoe; Noenoeng Rahajoe (Indonesian Pediatric Society, 1982)
Kartagener's syndrome is manifested by the associalion of sinusitis, situs inversus and bronchiectasis. The case described below occurred in a boy. Asplenia was also suspected with a strong family history of chronic respiratory infection. One of the four dead siblings and grandmother from mother's side has similar symptoms of respitatory infection and foul smelling breath. Symptoms of respiratory infection and running nose had started since infancy.